Preparation of Composite Films of Rod-like Structure of ZnO and Corn Starch for Bending Sensor - Feemuchang, Kitikamol; Onlaor, Korakot; Tunhoo, Benchapol; Thiwawong, Thutiyaporn (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
In this work, rod-like structure zinc oxide (R-ZnO) was synthesized by a hydrothermal process with the hydrothermal times of 3, 5, and 10 h. The effect of reaction time was reflected in the physical properties of the prepared R-ZnO, such as crystalline structure, shape geometries, and optical properties. Then, a bending device was fabricated with starch composite films and the rod-like structure of zinc oxide with different R-ZnO concentrations. The fabricated device exhibited flexibility characteristics at various bending angles. The composite film of corn starch and 1%wt. R-ZnO at a hydrothermal reaction time of 10 h demonstrated a high sensitivity at 89.5% with a gauge factor of 1.58. Moreover, the device of corn starch composited with R-ZnO exhibited fast response/recovery time of 0.23/0.15 s with high stability of bending cycle of more than 1,600 cycles. Therefore, the composite films of R-ZnO and natural starch are strong potential candidates for bending devices.